NEW U-PB DATA ON THE FORMATION OF THE PREDIVINSK PALEOISLAND-ARC COMPLEX (YENISEI RIDGE) - Vernikovsky V.A.; Vernikovskaya A.E.; Sal'nikova E.B.; Kotov A.B.; Chernykh A.I.; Kovach V.P.; Berezhnaya N.G.; Yakovleva S.Z. (My University, 1999)
New data on the formation and age of volcanics from the differentiated calc-alkalic series of Predivinsk terrane (Yenisei Ridge) are given. New petro- and geochemical data show a genetic unity of the volcanic series, which is interpreted as a paleoisland-arc complex. The morphology of zircon and its isotopic-geochemical study give grounds to treat the U-Pb data on the rhyolite age to be an estimate of the formation of the Predivinsk paleoisland-arc complex.